Research on the income and expenditure forecast of long-term care insurance fund in Shihezi City based on community care - Yang, Xu; Zuo, Penghua; Xie, Huiling (Frontiers in Public Health, 2024)
In the process of accelerating the aging process, how to actively respond to aging is a challenge faced by countries. China is conducting pilot work on long-term care insurance, but there is a problem of limited compensation during the pilot process, which makes it difficult to meet the needs of long-term disabled elderly people. This study predicts and analyzes the income and expenditure situation of the long-term care insurance fund in Shihezi City, and proposes suggestions for local long-term care insurance financing standards, which improves the development of long-term care insurance in Shihezi City and provides a basis for the sustainable development of long-term care insurance in China.